Capacity and operation of the Thonburi bus terminal - Prathip Chiradejnant; Drew, Donald R.; Jones, John Hugh; Subin Pinkayan (Bangkok : Asian Institute of Technology, 1969)
The purposes of this research are to describe the existing capacity and operation of the Thonburi City terminal for upcountry and local buses, to formulate a plan for increasing the terminal capacity, and to suggest means or increasing the efficiency of the terminal facilities. Three aspects of this research were the study of the unloading facility, the loading facility, and the inside terminal facility. Regarding the first, the movement of the incoming buses to the bays where they are unloaded is affected by the arrival and service patterns. The unloading operation was modeled as a queueing system and a classical queueing theory approach was utilized to determine the optimum number of bays. It was found that two unloading bays are adequate. Regarding the second aspect, bus operation indices were developed as figures of merit or criteria for deciding how many loading bays should be provided. The result suggests the number of bays needed to ensure a reasonable loading time to be seven. Regarding the third aspect, the inside terminal facility; the study of the terminal capacity involved the development of a deterministic queueing models to determine the space requirements. The findings indicate that 116 places are needed. A plan for renovating the terminal, based on the results of this research, would provide in the terminal capacity 98 parking places, 15 places for queue forming and 9 bays for loading and unloading facilities. Thus, it would appear that the proposed plan would provide sufficient capacity and because of the increase in the number of terminal parking places, would effect an improvement in operation by a factor of about two.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1969
Keywords: Motor bus terminals -- Thailand -- Thonburi